Evaluasi Prolanis Hipertensi Berbasis Teori Chain of Events di Puskesmas Playen II - Nufika Fatasyadhuha; Sutopo Patria Jati; Nurhasmadiar Nandini (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
According to the 2018 Riskesdas data, hypertension is a non-communicable disease with a significant increase in trend. Considering this case, hypertension has an urgency to be treated because it is a risk factor for the highest cause of death and disability according to the Institute for Health Metrics and Evaluation 2019. In this case Prolanis can be used as an alternative treatment for hypertension because it meets the criteria for the benefits of non-pharmacological therapy. We chose Puskesmas Playen II in Gunungkidul Regency as our research site because the coverage of providing hypertension services through Prolanis is still low, considering from the secondary data from the Gunungkidul Regency Health Office in 2020 where the percentage of hypertension services at the Puskesmas Playen II was only 0.3%, far below the 29 other puskesmas in Gunungkidul Regency. Hence, the study aimed to evaluate Prolanis' achievements in hypertension in Puskesmas Playen II using the Chain of Events evaluation theory. This research is qualitative with an evaluation study design. There were 15 informants as research subjects selected by purposive sampling. Prolanis' achievements in hypertension at Puskesmas Playen II have not reached the minimum target of 5% based on BPJS Kesehatan Regulation Number 7 of 2019, because the number of Prolanis-registered hypertensive patients is increasing but not matched with the increasing number of controlled hypertension sufferers. The Prolanis component also influences its unattainable achievement in follow-up treatment, so it is necessary to conduct routine monitoring of Prolanis participants’ lifestyles.